INVOLVING PLAY IN TEACHING ENGLISH TO ACCOMMODATE YOUNG STUDENTS’ LEARNING STYLE - Reni Buspita Sari; An Fauziah Syafei (Universitas Negeri Padang, 2012)
The purpose of this paper is to explain three kinds of play- musical chair, chain messege, and snake and ladder- and how to involve them in teaching English in order to accommodate students learning style (visual, auditory, and kinesthetic) for young students. It is hoped that it can inspire teacher to involve play in their teaching.AbstrakTujuan dari penulisan makalah ini adalah untuk menjelaskan bagaimana caranya melibatkan ketiga jenis permainan, yaitu musical chair, chain message, dan snake and ladder ke dalam pengajaran bahasa Inggris agar dapat mengakomodasi ketiga jenis gaya belajar siswa yaitu kinestetik, auditori, dan visual. Makalah ini disusun berdasarkan sejumlah kajian pustaka yang nantinya diharapkan dapat menginspirasi guru untuk melibatkan permainan dalam pengajaran bahasa Inggris.